Influence of SRT and HRT on Bioprocess Performance in Anaerobic Membrane Bioreactors Treating Municipal Wastewater. (1st February 2016) - Dong, Qirong; Parker, Wayne; Dagnew, Martha
ABSTRACT: : This study investigated the impact of Solid Retention Time (SRT) (40 to 100 days) and Hydraulic Retention Time (HRT) (2.5 to 8.5 hours) on the treatment of municipal wastewater in pilot and bench scale AnMBRs. The results revealed good permeate quality with respect to concentrations of COD (<40 mg/L) and BOD5 (<10 mg/L) was achieved under all conditions. Over the range of values tested SRT and HRTdid not significantly influence COD and BOD5 removal efficiencies. Extended SRTs resulted in reduced sludge production and enhanced methane production. Oversaturation of dissolved methane in permeate appears to have been responsible for a consistent lack of COD mass balance closure in all tests. After calibration of biokinetic coefficients, PetWin 4 (EnviroSim Canada) was found to effectively simulate the concentrations of particulate COD, readily biodegradable COD and acetic acid over a range of SRTs and HRTs. The calibrated saturation coefficients for hydrolysis and aceticlastic methanogenesis processes were comparable to those reported in literature. The saturation coefficient of fermentation was significantly lower than those reported in literature. The simulated methane mass flows were consistently higher than the measured values which was consistent with the lack of COD mass balance closure and was attributed to reduction of sulfate and oversaturation of the permeate with respect to Henry's Law.